2015
DOI: 10.1055/s-0041-104892
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Scientific Topics and Literature in Abdominal Radiology in Germany – Part 1: Gastrointestinal Tract

Abstract: The working group for abdominal and gastrointestinal diagnosis is a group of the German Radiological Society (DRG) focusing clinically and scientifically on the diagnosis and treatment of the gastrointestinal tract with all parenchymatous abdominal organs. In addition to the clinical and scientific further development of abdominal radiology, the education of radiologists within this core discipline of radiology is one of the major aims. In this article we give an up-to-date literature review of scientific radi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 110 publications
0
1
0
2
Order By: Relevance
“…Bei fulminanten Prozessen tritt das Gas bis in die Mesenterialvenen über und gelangt sogar bis in die extra-und intrahepatische Pfortader und verursacht das Vollbild porto-mesenterico-venösen Gases (PMVG). Obwohl reversible Fälle beschrieben sind gilt das gemeinsame Auftreten von PI und PMVG in der Literatur als prognoseverschlechternder Indikator [2,3,5].…”
Section: Ischämie Als Ursache Für Eine Reversible Pneumatosis Intestiunclassified
“…Bei fulminanten Prozessen tritt das Gas bis in die Mesenterialvenen über und gelangt sogar bis in die extra-und intrahepatische Pfortader und verursacht das Vollbild porto-mesenterico-venösen Gases (PMVG). Obwohl reversible Fälle beschrieben sind gilt das gemeinsame Auftreten von PI und PMVG in der Literatur als prognoseverschlechternder Indikator [2,3,5].…”
Section: Ischämie Als Ursache Für Eine Reversible Pneumatosis Intestiunclassified
“…), в качестве альтернативы возможно проведение МР-ангиографии [9,38]. Появление мультидетекторной КТ (МДКТ) в значительной мере заменило КТ-ангиографию в диагностике ХИОП, однако последняя сохраняет свою высокую диагностичекую значимость с учетом совершенствования методов внутрисосудистых вмешательств [41,42].…”
Section: современные подходы алгоритмы и методы диагностикиunclassified
“…Magnetic Resonance (MR) and Computed Tomography (CT) techniques, optimised for gastrointestinal imaging, are playing today an increasing role in the evaluation of gastrointestinal disorders, and several studies have shown the advantage of these techniques over tradition barium fluoroscopic examinations secondary to improvements in spatial and temporal resolution combined with improved bowel distending agents. Based on recent literature and guidelines, there is a change of paradigms regarding the diagnosis of esophagus and gastrointestinal cancer towards CT, whereas for small bowel imaging in inflammatory disease MRI with a new focus on Diffusion Weighted Imaging (DWI) are the most important imaging modalities, because DWI can be easily implemented in standard MRI for routine use to further enhance the diagnostic accuracy in disease assessment [ 1 4 ]. CT and MRI play an important role also in functional disorders.…”
mentioning
confidence: 99%